Prescribed Protein Intake Does Not Meet Recommended Intake in Moderate‐ and Late‐Preterm Infants: Contribution to Weight Gain and Head Growth. (3rd March 2020) - Gerritsen, Linda; Lindeboom, Robert; Hummel, Thalia
Abstract: Background: The purpose of the study was to evaluate differences between prescribed and recommended protein intake in moderate‐preterm (MP) and late‐preterm (LP) infants and examine the contribution of the first week's prescribed protein intake to growth until term age. Methods: Data on intake and anthropometrics were collected retrospectively in 235 preterm infants admitted to our general hospital's neonatal ward: 60 MP (32 0/7 –33 6/7 weeks' gestational age) and 175 LP (34 0/7 –36 6/7 weeks' gestational age). Differences between prescribed and recommended protein intake during the first postnatal week and z‐ score change for weight and head circumference (HC) between birth and term age were calculated. Multiple regression was used to evaluate the independent contribution of first week's prescribed protein intake to growth until term age. Results: At day 7, 58% of MP and 19% of LP infants reached recommended protein intake. At term age, mean z‐ score change was −0.4 for weight and +0.1 for HC. Mean protein intake (g/kg/d) was associated with z‐ score change of +0.34 (95% CI, 0.14–0.53; P < .001) for weight and +0.25 (95% CI, 0–0.5; P = .03) for HC. Reaching recommended protein intake at day 7 was only independently associated with weight z‐ score change (+0.22 [95% CI, 0.04–0.41; P = .002]). Conclusion: First week's prescribed protein intake does not meet recommended intake. Higher protein intakes in the first postnatal week result in increased weight gain and head growth until term age. Desirability and feasibility of increasing the protein intake need careful consideration and further discussion.